2017
DOI: 10.17816/ov10213-21
|View full text |Cite
|
Sign up to set email alerts
|

Results of presbyopia correction with multifocal profile application on the cornea by photorefractive keratectomy in hyperopic patients

Abstract: Purpose. To compare efficacy, safety and predictability of hyperopia and presbyopia simultaneous correction by photorefractive keratectomy (PRK) with application of a bi-aspheric multifocal profile on the cornea using PresbyMax software, and hyperopia correction by LASIK. Methods. 25 patients (50 eyes) of the 1st group were operated by PRK with bi-aspheric multifocal profile application on the cornea using PresbyMax software for simultaneous hyperopia and presbyopia correction. The 2nd group included 25 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…In 2017, Eskina et al reported the efficacy, predictability, and safety of presbyPRK compared with standard LASIK (nonmultifocal aspheric profile). 15 The Amaris laser PresbyMAX algorithm (Schwind eye-tech-solutions GmbH & Co. KG) was used by the authors. The addition for near vision was 1.50 D for the dominant eye and 2.30 D for the nondominant eye.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Eskina et al reported the efficacy, predictability, and safety of presbyPRK compared with standard LASIK (nonmultifocal aspheric profile). 15 The Amaris laser PresbyMAX algorithm (Schwind eye-tech-solutions GmbH & Co. KG) was used by the authors. The addition for near vision was 1.50 D for the dominant eye and 2.30 D for the nondominant eye.…”
Section: Discussionmentioning
confidence: 99%
“…На эксимерлазерных установках серии Schwind Amaris Е500 (Германия) предусмотрено формирование анизометропии ≈0,75 Дптр. со слабой миопической рефракцией вдаль на недоминантном глазу [9].…”
unclassified